Knowledge sharing behavior of service sector’s employees to attain sustainable development goals - Mahajan, Vibha; Sharma, Jyoti; Singh, Abhilasha; Bresciani, Stefano; Alam, Gazi Mahabubul (Emerald Publishing, 2024)
Purpose: The purpose of this study is to get an understanding regarding the clusters of middle management employees on the basis of their knowledge sharing behaviour. Designing knowledge sharing behaviors with a distinct focus for a specified group of employees can be an effective and productive one. As it is often argued that the cluster of employees labeled as “middle management” is the key player for knowledge sharing behaviors – a subject of this study that intends to contribute to management strategy to enhance organizational effectiveness and subsequently to its knowledge sharing phenomona. Design/methodology/approach: Cluster analysis was adopted as key tool as a part of quantitative method to accumulate the data from 597 employees who are working within the middle management of service sector located in the union territory of India named Jammu and Kashmir. Findings: Three distinct segments namely – “knowledge sharing adepts (KSA),” “knowledge sharing scrupulous (KSC)” and “knowledge sharing servitudes (KSE)” as the prime domains of knowledge sharing behavior are identified. Research limitations/implications: To draw a narrow focus, the study was limited to the service sector of a union territory in India, hence the findings may not be generalized. Furthermore, as knowledge sharing behavior of individuals is always evolved out of social and historical practices, findings of this cross-sectional study should ideally be needed to be updated time to time through further research. Practical implications: Cluster dynamicism of knowledge sharing behavior based on the differentiated and specified group of employee functions distinctly which in turn increases the organizational productivity with a particular focus on the mid-management of the service sector – a key managerial implication of this study. Originality/value: To the best of the authors’ knowledge, this research paper is the first of its kind in Jammu and Kashmir adding value to the international literature in the area of knowledge sharing behaviors of service sector. © 2024, Emerald Publishing Limited.